Excellence Initiatives to Create World-Class Universities - Salmi, Jamil (International Higher Education, 2016)
In the era of global rankings, many governments want to make sure that their top universities are actually operating at the cutting edge of intellectual and scientific development. A major concern has therefore been to identify the most effective method for inducing substantial and rapid progress in a country’s top universities. In order to accelerate the process of improving their top universities, several governments have launched so-called “excellence initiatives”, consisting of large injections of additional funding to boost their university sector. This article assesses the impact of these initiatives on the universities involved and on the rest of the tertiary education system. While the first section analyzes the main features of excellence initiatives, the second part examines their results as well as their limitations.